UMPs academic strategic collaboration intensifies internationalisation initiative - Hazmin, Aris (UMPSA, 2022)
SAUDI ARABIA, 14 May 2022 – Universiti Malaysia Pahang (UMP) is intensifying its academic and international strategic collaboration program in Jeddah, Saudi Arabia which has been established since 2008 to ensure continued cooperation.